2010
DOI: 10.1016/j.envpol.2009.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Field-scale leaching of arsenic, chromium and copper from weathered treated wood

Abstract: Earlier studies documented the loss of wood preservatives from new wood. The objective of this study was to evaluate losses from weathered treated wood under field conditions by collecting rainfall leachate from 5 different wood types, all with a surface area of 0.21 m 2 . Wood samples included weathered chromate copper arsenate (CCA) treated wood at low (2.7 kg/m 3 ), medium (4.8 kg/m 3 ) and high (35.4 kg/m 3 ) retention levels, new alkaline copper quat (ACQ) treated wood (1.1 kg/m 3 as CuO) and new untreate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 16 publications
0
27
0
1
Order By: Relevance
“…Likewise, this compound was widely used in Japan ; as arsenic was not present in the formula, ACQ contains a high copper concentration, much like CuAz. Copper-leaching has shown to be continuous from treated wood due to rainfall, albeit in lesser quantities as wood weathers (Hasan et al 2010 ).…”
Section: Atmosphere Contaminationmentioning
confidence: 98%
See 1 more Smart Citation
“…Likewise, this compound was widely used in Japan ; as arsenic was not present in the formula, ACQ contains a high copper concentration, much like CuAz. Copper-leaching has shown to be continuous from treated wood due to rainfall, albeit in lesser quantities as wood weathers (Hasan et al 2010 ).…”
Section: Atmosphere Contaminationmentioning
confidence: 98%
“…Studies have shown that creosote's main elements continuously leach from weather-treated wood when washed with rainfall, having the highest loss rate of any chemical wood treatment (Hasan et al 2010 ). Considering that some of its compounds are highly mobile in soil, they could threaten resources (Schiøtz Hanse and Ottosen 2002 ) and a number of its constituents, notably the O-and N-heterocyclics, which exhibit appreciable solubility, may be transported over signifi cant distances via surface runoff or groundwater (Enzminger and Ahlert 1987 ).…”
Section: Creosote Oilmentioning
confidence: 99%
“…In addition, the interval between rainfall events has been reported to influence leaching, with greater amounts leached after longer resting periods. This type of effect has been attributed to the allowance for a longer period for soluble preservative components to diffuse to the surface from the interior of the wood products (Chung and Ruddick 2004, Hasan et al 2010, Ruddick 2008, Tao et al 2013, Taylor and Cooper 2005. At least one study, however, found little relationship between the length of the interval between rainfall events and the subsequent concentrations of preservative metals in leachate (Morrell et al 2010).…”
Section: Universidad Del Bío -Bíomentioning
confidence: 99%
“…Field leaching tests indicating that time between rainfall events influences leaching have been conducted over longer times periods, and included longer periods between rainfall events (Chung and Ruddick 2004, Hasan et al 2010, Taylor and Cooper 2005. Time is required for mobilized preservative components to diffuse through the wood to the surface, and although the volume of rainfall was similar to a year of exposure, the length of time for diffusion of mobilized components through the wood was shorter than that of a specimen exposed for a year outdoors.…”
Section: Universidad Del Bío -Bíomentioning
confidence: 99%
See 1 more Smart Citation